Teachers’ attitudes, perceptions and experiences in CLIL: a look at content and language - McDougald, Jermaine S. (Colombian Applied Linguistics Journal, 2015)
This paper is a preliminary report on the “CLIL State of the Art” project in Colombia, drawing on data collected from 140 teachers’ regarding their attitudes toward, perceptions of, and experiences with CLIL (content and language integrated learning). The term CLIL is used here to refer to teaching contexts in which a foreign language (in these cases, English) is the medium for the teaching and learning of non-language subjects. The data that has been gathered thus far reveal that while teachers presently know very little about CLIL, they are nevertheless actively seeking informal and formal instruction in CLIL. Many of the surveyed teachers are currently teaching content areas through English; approximately half of them reported having had positive experiences teaching content and language together, though the remainder claimed to lack sufficient knowledge in content areas. Almost all of the participants agreed that the CLIL approach can benefit students, helping them develop both language skills and subject knowledge (meaningful communication). Nevertheless, there is still considerable uncertainty as to the actual state of the art of CLIL in Colombia; greater clarity here will enable educators and decision-makers to make sound decisions for the future of general and language education.